Mergers and the incentives to undertake product innovation oriented R&D: First steps towards an assessment approach - Benjamin René Kern; Juan Manuel Mantilla Contreras (Philipps-University Marburg, Faculty of Business Administration and Economics, 2014)
The firms that compete with one another in terms of innovation do not necessarily coincide with the relevant competitors on pre-innovation product markets. As a consequence, the findings about the ambiguous interrelation between (product) market concentration and innovation cannot be transferred one-to-one to the interrelationship between innovation competition and innovation. By identifying and classifying the most relevant effects, which are decisive for the impact of mergers on the incentives to invest in product innovation oriented R&D, we will demonstrate that the interrelation between innovation competition and innovation is not always as unclear as it seems. Hence, by analyzing the model-theoretic industrial organization literature, this article aims to contribute to the discussion about the development of a decision theoretic assessment framework for analyzing the impact of mergers on innovation and is therefore also in line with the idea of a rule-based competition policy which is, from a law and economics perspective, ought to reduce error costs, give legal guidance and reduce legal uncertainty.
Keywords: K21; L12; L41; O31; 330